Bilberry (Vaccinium myrtillus L.) Powder Has Anticarcinogenic Effects on Oral Carcinoma In Vitro and In Vivo - Matti Mauramo; Tuulia Onali; Wafa Wahbi; Jenni Vasara; Anniina Lampinen; Elina Mauramo; Anne Kivimäki; Stefan Martens; Hely Häggman; Meeri Sutinen; Tuula Salo (MDPI AG, 2021)
Previous studies indicate that bilberry with high amounts of phenolic compounds can inhibit carcinogenic processes of colorectal cancer in vitro and in vivo. However, no studies have focused on the effects of bilberry on oral cancer. In this study, we aimed to examine the effects of bilberry powder on oral squamous cell carcinoma (OSCC) cells using both in vitro and in vivo assays. The effects of 0, 1, 10, and 25 mg/mL of whole bilberry powder on the viability, proliferation, migration, and invasion of OSCC (HSC-3) cells were examined and compared with 0.01 mg/mL of cetuximab. Two oral keratinocyte cell lines served as controls. Tumor area was analyzed in zebrafish microinjected with HSC-3 cells and treated with 2.5, 10, or 25 µg/mL of bilberry powder. Metastases in the head or tail areas were counted. Bilberry powder inhibited the viability, proliferation, migration, and invasion of HSC-3 cells (p < 0.05), which was more pronounced with higher concentrations. Cetuximab had no effect on HSC-3 cell migration or invasion. Compared to controls, the tumor area in zebrafish treated with bilberry powder (10 and 25 µg/mL) was reduced significantly (p = 0.038 and p = 0.021, respectively), but the number of fish with metastases did not differ between groups. Based on our in vitro and in vivo experiments, we conclude that whole bilberry powder has anti-tumor effects on OSCC cells.